2016
DOI: 10.1007/s12035-016-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Methylmercury in Isolated Astrocytes and Neurons: the Cytoskeleton as a Main Target

Abstract: In the present work, we focused on mechanisms of methylmercury (MeHg) toxicity in primary astrocytes and neurons of rats. Cortical astrocytes and neurons exposed to 0.5-5 μM MeHg present a link among morphological alterations, glutathione (GSH) depletion, glutamate dyshomeostasis, and cell death. Disrupted neuronal cytoskeleton was assessed by decreased neurite length and neurite/neuron ratio. Astrocytes presented reorganization of actin and glial fibrillary acidic protein (GFAP) networks and reduced cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 75 publications
1
15
0
1
Order By: Relevance
“…Indeed, exposure to 100 nM MeHg for 24 h induced apoptosis in differentiating PC12 cells, and decreased Akt phosphorylation [ 116 ]. Corroborating these findings, Pierozan et al, 2017 have also demonstrated that MeHg reduced neuronal viability and induced caspase 3-dependent apoptosis with downregulated PI3K/Akt pathway in primary cortical neurons treated with 1 µM MeHg for 24 h. In this study, the authors noted increased oxidative damage, suggesting that MeHg downregulated Akt phosphorylation despite the noted increase in ROS production [ 117 ]. A recent in vivo study using 30-day-old pups from pregnant rats treated with 2 mg/kg MeHg from gestational day 5 until parturition, has shown that the pups prenatally exposed to MeHg failed to increase hippocampal oxidative stress, while the levels of Akt phosphorylation were decreased.…”
Section: Mehg and Pi3k/akt Signaling Pathwaysupporting
confidence: 61%
“…Indeed, exposure to 100 nM MeHg for 24 h induced apoptosis in differentiating PC12 cells, and decreased Akt phosphorylation [ 116 ]. Corroborating these findings, Pierozan et al, 2017 have also demonstrated that MeHg reduced neuronal viability and induced caspase 3-dependent apoptosis with downregulated PI3K/Akt pathway in primary cortical neurons treated with 1 µM MeHg for 24 h. In this study, the authors noted increased oxidative damage, suggesting that MeHg downregulated Akt phosphorylation despite the noted increase in ROS production [ 117 ]. A recent in vivo study using 30-day-old pups from pregnant rats treated with 2 mg/kg MeHg from gestational day 5 until parturition, has shown that the pups prenatally exposed to MeHg failed to increase hippocampal oxidative stress, while the levels of Akt phosphorylation were decreased.…”
Section: Mehg and Pi3k/akt Signaling Pathwaysupporting
confidence: 61%
“…These results suggest that the calpain-mediated decrease in MARCKS amount mediates MeHg toxicity to SH-SY5Y cells at the low concentration of this chemical. Recently, Pierozan et al proposed that the cytoskeleton is an end point of MeHg cytotoxicity [ 28 ]. Because it has been demonstrated that in vitro cleavage of MARCKS by calpain increases its actin-binding activity [ 41 ], MARCKS cleaved by calpain may exert its effect via actin reorganization, in addition to the increase in MARCKS phosphorylation [ 34 ] in MeHg toxicity to SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also consistent with reports that have shown down-regulation of Akt in response to MeHg, such as decreased Akt phosphorylation in the hippocampus of 30-day-old rat pups prenatally exposed to MeHg ( Heimfarth et al, 2018a ). MeHg also reduced Akt phosphorylation in vitro in primary neurons, at concentrations associated with cell death ( Pierozan et al, 2017 ). Nonetheless, further studies are necessary to elucidate the biochemical mechanisms associated to the regulation of Akt signaling induced by MeHg.…”
Section: Cytoprotective Responses To Mehgmentioning
confidence: 99%